What women want: Unveiling predisposition to vaginal birth in an Italian population - Paola Romeo; Simona Bulla; Patrizia Marra; Rosario D'Anna (Advances in Medicine, Psychology, and Public Health)
Introduction: In the world, the rates of Cesarean sections are rising. In Italy, we have the highest percentage of abdominal delivery in Europe. Studies show that the increasing request for cesarean section by women contributes to this phenomenon. The purpose of this study was to analyze the predisposition of women to vaginal birth, the factors that influenced their preferences, and the role of the information. Methods: We used questionnaires compiled by pregnant women [nulliparous and multiparous] of any gestational era. The questionnaire was made of four parts: personal data, obstetric anamnesis, information received during gestation, and emotional aspects. Results: We administered 802 questionnaires. Questionnaires considered valid for inclusion were 754. The percentage of women predisposed to cesarean section was 17.6% (nulliparous) and 20.3% (multiparous). Considering nulliparous, cesarean section preference was statistically associated with advanced maternal age [O.R. 2.17, p 0.005], smoking during pregnancy [O.R. 2.37, p 0.02], the beginning of pregnancy [O.R. 3.16 p 0.0045], the information that aroused their anxiety and fear [O.R. 3.50, p <0.0001], the fear of vaginal delivery [O.R. 6.66, p <0.0001], not having attended to the pre-birth course [ O.R. 2.24, p 0.0007], the thought that cesarean section is physically [O.R. 6.45, p <0.0001] and psychologically [O.R. 7.02, p <0.0001] simpler than vaginal delivery and safer for the baby [O.R.6.33, p <0.0001], and the belief to have the right to choose the modality of giving birth [O.R. 3.86, p 0.0022]. Considering multiparous women, statistically significant associations were found between cesarean section and foreign women [O.R. 3.62, p 0.02], information received about labor and childbirth that aroused their anxiety and fear [O.R. 2.85, p 0.0005], fear of childbirth [O.R. 3.28, p 0.0003], the thought that cesarean section is physically [O.R. 16.62, p <0.0001] and psychologically [O.R. 13.66, p <0.0001] simpler than vaginal delivery and safer for the baby [O.R.6.43, p <0.0001], and the belief to have the right to choose the modality of giving birth [O.R. 4.20, p 0.003]. Discussion: A growing portion of women wish to deliver by cesarean section. This is due to anthropological and social aspects. We analyzed that the role of the information in this predisposition is relevant. For this reason, we believe that emphatic, careful, correct information can reduce this tendency.